Kawīniphon khun Phum - Khun Phum,Thipphawan Bunsongčharœ̄n (Krom Sinlapākō̜n, 2020)
History and criticism of poems by Khun Phum, 19th century Thai poet, contains her brief biography
Poems
Keywords: Biografie; Khun Phum; Poets; Thai; Thai poetry; Thai literature